Lateral flow test performance in children for SARS-CoV-2 using anterior nasal and buccal swabbing: sensitivity, specificity, negative and positive predictive values. Issue 2 (9th September 2022) - Harwood, Rachel; Rad, Laura; Kelly, Christopher; Shelton, Cliff; Shepherd, Elizabeth; Roderick, Marion; Whittaker, Elizabeth; Dyke, Steven; Patel, Sanjay Vallabh; Gent, Nick; Kenny, Simon E
Abstract : Objective: To determine if the sensitivity of the lateral flow test is dependent on the viral load and on the location of swabbing in the respiratory tract in children. Design: Phase 1: Routinely performed reverse transcriptase PCR (RT-PCR) using nose and throat (NT) swabs or endotracheal (ET) aspirates were compared with Innova lateral flow tests (LFTs) using anterior nasal (AN) swabs. Phase 2: RT-PCR-positive children underwent paired AN RT-PCR and LFT and/or paired AN RT-PCR and buccal LFT. Setting: Tertiary paediatric hospitals. Patients: Children under the age of 18 years. Phase 1: undergoing routine testing, phase 2: known SARS-CoV-2 positive. Results: Phase 1: 435 paired swabs taken in 431 asymptomatic patients resulted in 8 positive RT-PCRs, 9 PCR test failures and 418 negative RT-PCRs from NT or ET swabs. The test performance of AN LFT demonstrated sensitivity: 25% (4%–59%), specificity: 100% (99%–100%), positive predictive value (PPV): 100% (18%–100%) and negative predictive value (NPV): 99% (97%–99%). Phase 2: 14 AN RT-PCR-positive results demonstrated a sensitivity of 77% (50%–92%) of LFTs performed on AN swabs. 15/16 paired buccal LFT swabs were negative. Conclusion: The NPV, PPV and specificity of LFTs are excellent. The sensitivity of LFTs compared with RT-PCR is good when the samples are colocated but may be reduced when the LFT swab is taken from the AN. Buccal swabs are not appropriate for LFT testing. Careful consideration of the swabbing reason, the tolerance of the child and the requirements for test processing (eg, rapidity of results) should be undertaken within hospital settings. Trial registration number: NCT04629157 . Abstract : Swabbing children for SARS-CoV-2, what might lateral flow tests tell us?